Hobson and the Fabians: Two Roads to Socialism in the 1920s - Noel Thompson (History of Political Economy, 1994)
The article contrasts Fabian political economy with the liberal socialism of J.A. Hobson and considers the prescriptive implications of each with respect to the conduct of macroeconomic policy in the inter-war period.